Electronic control on linear versus branched alkylation of 2-/3-aroylbenzofurans with acrylates: combined DFT and synthetic studies - Srinivas, Kolluru; Dangat, Yuvraj; Kommagalla, Yadagiri; Vanka, Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2017)
Investigations on the factors that govern unusual branched alkylation of 2-aroylbenzofurans with acrylates by Ru-catalyzed carbonyl-directed C-H activation has been carried out by calculating the kinetics associated with the two key steps-the coordination of the acrylate with the intermediate ruthenacycle and the subsequent migratory insertion reaction-studied with the help of DFT calculations. Eight possible orientations for each mode of alkylation have been considered for the calculations. From these calculations, it has been understood that there is a synergistic operation of the steric and electronic effects favoring the branched alkylation. Further DFT investigations on the alkylation of the isomeric 3-aroylbenzofurans indicated a preference for the linear alkylation and this has been verified experimentally. Overall, the observed/calculated complementary selectivity in the alkylation of 2-/3-aroylbenzofurans with acrylates reveals that the substrate-dependent charge distribution of the Ru-C bond in the intermediate ruthenacycle is an important determining factor and thus the current work opens up a new domain of substrate design for controlling regioselectivity.
Keywords: acrylates; Alkylation; aroylbenzofuran; C-H activation; Density functional calculations

Intrinsically microporous polyimides containing spirobisindane and phenazine units: synthesis, characterization and gas permeation properties - Shrimant, Bharat; Dangat, Yuvraj; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A - Polymer Chemistry, 2018)
A new diamine containing spirobisindane and phenazine units, namely, 3,3,3,3-tetramethyl-2,2,3,3-tetrahydro-1,1-spirobi[cyclopenta[b]phen azine]-7,7-diamine (TTSBIDA) was synthesized starting from commercially available 5,5,6,6-tetrahydroxy-3,3,3,3-tetramethyl-1,1-spirobisindane (TTSBI). TTSBI was oxidized to 3,3,3,3-tetramethyl-2,2,3,3-tetrahydro-1,1-spirobi[indene]-5,5,6,6-tet raone (TTSBIQ) which was subsequently condensed with 4-nitro-1,2-phenylenediamine to obtain 3,3,3,3-tetramethyl-7,7-dinitro-2,2,3,3-tetrahydro-1,1-spirobi[cyclope nta[b]phenazine] (TTSBIDN). TTSBIDN was converted into TTSBIDA by reduction of the nitro groups using hydrazine hydrate in the presence of Pd/C as the catalyst. A series of new polyimides of intrinsic microporosity (PIM-PIs) were synthesized by polycondensation of TTSBIDA with commercially available aromatic dianhydrides. PIM-PIs exhibited amorphous nature, high thermal stability (T-10>480 degrees C) and intrinsic microporosity (BET surface area=59-289 m(2)/g). The gas permeation characteristics of films of selected PIM-PIs were evaluated and they exhibited appreciable gas permeability as well as high selectivity. The CO2 and O-2 permeability of PIM-PIs were in the range 185.4-39.2 and 30.6-6.2 Barrer, respectively. Notably, polyimide derived from TTSBIDA and 4,4-(hexafluoroisopropylidene)diphthalic anhydride (PIM-PI-6FDA) exhibited high CO2 and O-2 permeability of 185.4 and 30.6 Barrer with CO2/CH4 and O-2/N-2 selectivity of 43.1 and 5.1, respectively. The data of PIM-PI-6FDA for CO2/CH4 and O-2/N-2 gas pairs were located near Robeson upper bound. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 766-775
Keywords: Gas permeability; intrinsic microporosity; polyimides; spirobisindane

Direct oxidation of bromo-derived Fischer-Borsche oxo-ring using molecular iodine with combined experimental and computational study - Humne, Vivek T.; Ghom, Monica H.; Naykode, Mahavir S.; Dangat, Yuvraj; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2022)
A direct oxidation of the bromo-derived Fischer-Borsche oxo-ring leading to carbazolequinone has been developed by using molecular iodine. This unprecedented transformation has been used for the modular synthesis of the anti-cardiotonic agent murrayaquinone. Furthermore, the present method has been generalized to a broad range of functional groups, with good to excellent yield.